Dental Fear Survey: A Cross-Sectional Study Evaluating the Psychometric Properties of the Brazilian Portuguese Version - Maurício Antônio Oliveira; Miriam Pimenta Vale; Cristiane Baccin Bendo; Saul Martins Paiva; Júnia Maria Serra-Negra (The Scientific World Journal)
Objective. The aim of this study was to evaluate the psychometric properties of the Brazilian version of the Dental Fear Survey (DFS), previously translated to the Brazilian Portuguese language and validated. Methods. A cross-sectional study with 1,256 undergraduates from the city of Belo Horizonte, Brazil, was carried out. The DFS and a questionnaire about previous dental experiences were self-administered. Data analysis involved descriptive statistics, principal components analysis (PCA), confirmatory factor analysis (CFA), internal consistency and test-retest reliability, and construct, discriminant, and convergent validity. Results. PCA identified a three-factor structure. CFA confirmed the multidimensionality of the Brazilian version of the DFS. A modified model of the Brazilian version of the DFS fits better than the hypothesized model. The Cronbach’s alpha coefficient for the total DFS scale was 0.95. Conclusion. The DFS demonstrated acceptable construct validity, convergent validity, and discriminant validity. These results supported the reliability and validity of the DFS among Brazilian undergraduates.